Commentary on "Transpositions within user-posted YouTube lyric videos: A corpus study" - Yim, Gary K. (Empirical Musicology Review, 2016)
Responding to Plazak's corpus study on pitch and tempo transpositions in user-created music videos on YouTube, I suggest that such transpositions may have musically communicative intentions. Besides the nominal changes designed to defeat copyright infringement detection algorithms, I propose that pitch and tempo changes may be used for listener enjoyment. Some comments on the methodology of the experiment are included.